Unique outcomes in professional psychology training through an adventure experience - Human, Lourens (University of the Free State, 2008)
English: This article focuses on how an adventure programme can be used to address professional development in general, and specifically the professional identity of postgraduate psychology students. The literature study focuses on didactic instruction as well as experiential learning and adventure-based experiential learning. The study was undertaken from a narrative position and narrative analysis was done of postgraduate psychology students’ narratives. From the narrative analysis it would seem that the adventure programme created unique outcomes for the students, as their narratives changed from narratives with an individualist character to narratives with more collective tendencies as the adventure programme unfolded.

Afrikaans: Hierdie artikel fokus op die gebruik van ’n avontuur-gebaseerde program om professionele ontwikkeling in die algemeen en, meer spesifiek, professionele identiteit van nagraadse sielkunde studente aan te spreek. Die literatuurstudie skenk aandag aan didaktiese leer, asook aan ervaringsleer en avontuur-gebaseerde ervaringsleer. Die narratiewe metafoor het as teoretiese vertrekpunt in die studie gedien en ’n narratiewe analise is op die narratiewe van nagraadse sielkunde studente gedoen. Vanuit die narratiewe analise het dit geblyk dat die avontuur-gebaseerde program unieke uitkomste vir die studente geskep het. Die studente se narratiewe het verander van narratiewe met ’n individualistiese karakter tot narratiewe met ’n meer kollektiewe geneigdheid soos wat die avontuur-gebaseerde program ontvou het.
Keywords: Psychology students; Postgraduate students; Adventure-based experiential learning; Postgraduate psychology programmes